The Shadow of Dunblane - Macritchie, Iain A. M. (Journal of religion and health, 1997)
The massacre of sixteen children and their teacher in Scotland, at the Dunblane Primary School, earlier this year, shook the world. Hundreds of thousands of flowers were sent from all over the globe, as a gesture of sympathy and solidarity. Eight months later, the world carries on its normal business, but for the people of Dunblane there can be no return to normality. This article looks at some points raised by the Cullen Report, the Government inquiry into the massacre, particularly the emerging details about the background of the killer, Thomas Hamilton. These details are set alongside Jung's discussion of the Shadow archetype. The article also examines the role of the local churches at the time of the tragedy and thereafter, particularly the Cathedral at the center of Dunblane. The final section looks at some general reactions within the community to the killings.